2015
DOI: 10.21608/ejnf.2015.105816
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intermittent Feeding and Flash Lighting Regimens in Broiler Chickens Management

Abstract: wo experiments were conducted to evaluate the effect of intermittent feeding and flash lighting regimens on growth performance, carcass traits, blood parameters and economic efficiency of broiler chickens. In experiment 1, one hundred and twenty, one-day old Cobb chicks were equally distributed into four groups (each consisted of 3 replicates of 10 birds each). Chicks in the first group (G1) were fed ad libitum (Control, C), while the other three groups were fed according to intermittent feeding regimes consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…These findings partially agree with those reported by Farghly and Makled (2015) who they found that flash lighting significantly affected on liver percentages. And, Abreu et al, (2011) who showed that lighting programs did not affect the heart, liver, gizzard, and abdominal fat percentages.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings partially agree with those reported by Farghly and Makled (2015) who they found that flash lighting significantly affected on liver percentages. And, Abreu et al, (2011) who showed that lighting programs did not affect the heart, liver, gizzard, and abdominal fat percentages.…”
Section: Discussionsupporting
confidence: 93%
“…Our study in same line with Farghly et al, (2019a) who reported that lighting programs did not significantly change the carcass traits. Also, Farghly and Makled (2015) they found non-significant differences in the percentages of the dressed carcass, drumstick, femur, breast, heart, and gizzard among all groups under light flashes, although the differences were significant (P < 0.05) in the drumstick, liver and abdominal fat percentages. And, this result was consistent with the findings of Downs et al, (2006), who reported no significant effect in the cold carcass yield of birds exposed to different lighting program .…”
Section: Carcass Traitsmentioning
confidence: 86%
See 2 more Smart Citations
“…The obtained results are in agreement with Farghly et al, (2019a) who reported that broilers exposed to flashing light had the highest body weight. Using flashing light may have aided early growth by providing more opportunity for the birds to reduce heat production and stimulate the secretory patterns of several hormones (Farghly and Makled, 2015;Farghly et al, 2016). Providing intermittent light for 2L:2D has been shown to improve growth performance compared with 8L:16D (Olanrewaju et al, 2012;Olanrewaju et al, 2019b).…”
Section: Growth Performancementioning
confidence: 99%